Engineering-geological insights into the gypsum-bearing deposits of Punta delle Pietre nere (Puglia Region, Italy) - Calcaterra, Domenico; Corniello, Alfonso; Di Martire, Diego; Forte, Giovanni; Stevenazzi, Stefania; Tufano, Rita (Italian journal of engineering geology and environment, 2024)
In a very limited area near Punta delle Pietre Nere (Puglia region, Italy), chalky deposits crop out along with black limestones interspersed with bituminous marls and igneous rocks. From 1927 to 1930 these gypsums were affected by some works that modified the path of the Acquarotta Canal to connect the close lagoon (Lesina Lake) to the sea and facilitate its flow conditions. Over time, the strip of land close to the Acquarotta Canal was affected by sinkhole phenomena related to the dissolution of the chalk. These phenomena also occurred in the nearby town of Lesina Marina. Since 1990, numerous investigations have been carried out in the area, including geological, hydrogeological and geomechanical surveys, geo-electrical and seismic surveys, and remote sensing analyses. In this study, we present the results of recent site-specific investigations, which enabled to better understand the buried limits of the chalky deposits, their depth, the geological characteristics of the covering soils and the groundwater flow conditions. In summary, the distribution of gypsum-bearing deposits in the subsoil of the area is now better defined than in the past, when the uncertainty of the data represented a factor strongly limiting the local possibilities of settlements’ development.